7TH HIMALAYA KARAKORAM TIBET WORKSHOP - Searle, M; Treloar, P (1992)
The first Himalayan Workshop held in Leicester Univienrsity 1985 was so successful that it was then agreed to hold the informal conference and workshop annually. Subsequently the Himalayan Workshops were held in Vandoevre-les-Nancy, France in 1986, London (1987), Lausanne, Skvitzerland (1988), Milan, Italy (1990) and Grenoble, France (1991). The upsurge in research throughout the Himalayan and Tibetan regionins the last ten years has warranted these annual meetings, and the dissemination of new research throughout the Himalayan community has been invaluable. This year the meeting was held in the Department of Earth Sciences, Oxford University, under the auspices of The Geological Society, London. from 6-8 April 1992. Over 120 participants from 15 countries attended.